2020
DOI: 10.3390/v12090949
|View full text |Cite
|
Sign up to set email alerts
|

Study of a SARS-CoV-2 Outbreak in a Belgian Military Education and Training Center in Maradi, Niger

Abstract: Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) compromises the ability of military forces to fulfill missions. At the beginning of May 2020, 22 out of 70 Belgian soldiers deployed to a military education and training center in Maradi, Niger, developed mild COVID-19 compatible symptoms. Immediately upon their return to Belgium, and two weeks later, all seventy soldiers were tested for SARS-CoV-2 RNA (RT-qPCR) and antibodies (two immunoassays). Nine sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 16 publications
0
33
0
Order By: Relevance
“…Whole genome sequencing was performed on an Oxford Nanopore MinION device using R9.4 flow cells (Oxford Nanopore Technologies, UK) after a multiplex PCR with an 800bp SARS-CoV-2 primer scheme as previously described [25]. Sequence reads were basecalled in high accuracy mode and demultiplexed using the Guppy algorithm v3.6.…”
Section: Methodsmentioning
confidence: 99%
“…Whole genome sequencing was performed on an Oxford Nanopore MinION device using R9.4 flow cells (Oxford Nanopore Technologies, UK) after a multiplex PCR with an 800bp SARS-CoV-2 primer scheme as previously described [25]. Sequence reads were basecalled in high accuracy mode and demultiplexed using the Guppy algorithm v3.6.…”
Section: Methodsmentioning
confidence: 99%
“…To analyze possible patterns of spread, especially among the small clusters of SARS-CoV-2-positive soldiers returning from Niger [ 16 ] and Mali, and to analyze the possible introduction of new SARS-CoV-2 variants in Belgium, we further determined the whole-genome sequences of the SARS-CoV-2 isolates. Nineteen complete genome sequences were obtained from the 21 RT-qPCR-positive samples.…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative RT-PCR (RT-qPCR) was performed on the samples using two methods. Until October 2020, the Novel Coronavirus (2019-nCoV) Nucleic Acid Diagnostic Kit and Sample Release Reagent (both Sansure Biotech Inc., China) were used, according to the manufacturer’s instructions, including some modifications to cater for a LightCycler 2.0 instrument (Roche Diagnostics, Diegem, Belgium) [ 16 ]. The RT-qPCR assay amplifies the ORF1ab and N genes, which encode a well-conserved replicase polyprotein and the nucleocapsid protein, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The discussed mechanisms included the hijack of antigen-presenting cells to virus dissemination through mucosal tissues; escape from RNA sensors by shielding RNA intermediates in replication organelles and 2′-O-methylation modification of virus RNA; antagonization of interferon-mediated signal transduction, and inhibition of interferon stimulated genes (ISG). Pirnay et al [ 5 ] characterized a SARS-CoV-2 outbreak in a Belgian military education and training center in Maradi, Niger. Viral load could be detected in symptomatic and asymptomatic individuals, and analysis of the genome sequences suggested that the soldiers and trainers were infected in Africa.…”
mentioning
confidence: 99%